Processing of continuous fibre reinforced thermoplastics - Nunes, J. P. (2012)
Towpregs based on different fibres and thermoplastic matrices were processed for highly demanding and more commercial applications by different composite processing technologies. In the technologies used, compression moulding and pultrusion, the final composite pr ocessing parameters were studied in order to obtain composites with adequate properties at industrial compatible production rates. The produced towpregs were tested to verify its polymer content and degree of impregnation. The obtained results have shown t hat the coating line enabled to produce, with efficiency and industrial scale speed rates, thermoplastic matrix towpregs that may be used to manufacture composites for advanced and larger volume commercial markets.